(untitled) - Kennedy, Heather (Victoria, Australia, 2004)
Data in Three Dimensions: A Guide to ArcGIS 3D Analyst is a self-study workbook providing tutorial information and over 25 step-by-step exercises that show you how to manipulate surface data in a three-dimensional environment using ESRI’s 3D Analyst extension to ArcGIS. Readers learn how to create TIN, raster, and 3D vector data; set 3D display properties such as sun position and vertical exaggeration; and display ordinary two-dimensional features such as rivers, roads, and buildings in 3D. Readers will also learn to navigate in real time through 3D terrain, perform line-of-sight and volume analysis, and convert between raster, TIN, and vector formats. New to 3D Analyst 8.2, users will be shown how to create 3D animated films that can be exported as avi (Audio Video Interleave) movie files. Exercises are easy to understand, with detailed discussions of data types and software functionality throughout. Designed for use with ArcGIS Desktop software, this book makes a great accompaniment to ArcGIS 3D Analyst versions 8.1 and higher.
Keywords: Geographic information systems,Three-dimensional display systems,ArcGIS